If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x + -3x = 15(x + -3) + 13 + -7 Combine like terms: 20x + -3x = 17x 17x = 15(x + -3) + 13 + -7 Reorder the terms: 17x = 15(-3 + x) + 13 + -7 17x = (-3 * 15 + x * 15) + 13 + -7 17x = (-45 + 15x) + 13 + -7 Reorder the terms: 17x = -45 + 13 + -7 + 15x Combine like terms: -45 + 13 = -32 17x = -32 + -7 + 15x Combine like terms: -32 + -7 = -39 17x = -39 + 15x Solving 17x = -39 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 17x + -15x = -39 + 15x + -15x Combine like terms: 17x + -15x = 2x 2x = -39 + 15x + -15x Combine like terms: 15x + -15x = 0 2x = -39 + 0 2x = -39 Divide each side by '2'. x = -19.5 Simplifying x = -19.5
| 4y-2+y+30=6y+30-3y | | (2x)+(x+12)=123 | | (2x)-(x+12)=123 | | S(t)=-16t^2+25 | | -7v+46=-3(v-2) | | 9t-6t= | | 96-6t= | | (2x)+(x+12)+58=180 | | 18n^2-32=0 | | 3(x+5)-9=6 | | -9=n+9 | | 6/5x=4/7 | | 8x^2+2x-9=R | | 19x=133 | | 9x+3x-2(x-3)-5=4(2x-5)+13-2x | | -5y+5=2(4y+11) | | 1/5=y/20 | | 6x+y+1=0 | | 6+5=6 | | 7-(4x-3)=6-5x | | 3/2w-(-4/5) | | 4x+11=35+x | | 3(4x+8)=-8+20 | | 3x+y-2z= | | z+1=2z-7 | | F=295-2S | | 18x-19=15+2x | | 5(x+8)=30(x-2) | | 15x^2+3x-8=0 | | 9x=342 | | X^4+5x^3+4x^2-10x-12=0 | | 4x=x^2-110 |